Cross-Cultural Comparison of Mental Health Between German and South African Employees: Shame, Self-Compassion, Work Engagement, and Work Motivation - Kotera, Yasuhiro; Mayer, Claude-Hélène; Vanderheiden, Elisabeth (Frontiers in Psychology, 2021)
The negative impact of the coronavirus disease outbreak 2019 (COVID-19) on work mental health is reported in many countries including Germany and South Africa: two culturally distinct countries. This study aims to compare mental health between the two workforces to appraise how cultural characteristics may impact their mental health status. A cross-sectional study was used with self-report measures regarding (i) mental health problems, (ii) mental health shame, (iii) self-compassion, (iv) work engagement and (v) work motivation. 257 German employees and 225 South African employees have completed those scales. This study reports results following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. T-tests, correlation and regression analyses were performed. German employees had lower mental health problems and mental health shame, and higher self-compassion than South Africans. Mental health problems were positively associated with mental health shame and amotivation, and negatively associated with work engagement and intrinsic motivation in both groups. Lastly, self-compassion, a PP 2.0 construct, was the strongest predictor for mental health problems in both countries. Our results suggest i) that German culture's long-term orientation, uncertainty avoidance and restraint may help explain these differences, and ii) that self-compassion was important to mental health in both countries. While the levels of mental health differed between the two countries, cultivating self-compassion may be an effective way to protect mental health of employees in those countries. Findings can help inform managers and HR staff to refine their wellbeing strategies to reduce the negative impact of the pandemic, especially in German-South African organizations.